Inter-generational access to resources: developing criteria and indicators - Colfer, C.J.P.; Wadley, R.L.; Harwell, E.; Prabhu, Ravi (1997)
This paper makes use of data from a methodological pre-test conducted in and around Danau Sentarum Wildlife Reserve in West Kalimantan, Indonesia. Its purpose was to contribute to the development of principles, criteria and indicators for sustainable forest management (SFM). The particular topic investigated here is "inter-generational access to resources", an issue widely deemed important - and very difficult to assess - in sustainable forest management.The methods pre-tested are described, and earlier versions of the principles, criteria and indicators are re-evaluated, re-ordered and scored in a dual attempt: to develop simple, inexpensive and reliable assessment methods, and to contribute to our understanding of the causal links between inter-generational access to resources and sustainable forest management